Foraging aggressiveness determines trophic niche in a generalist biological control species. (24th February 2021) - Michalko, Radek; Gibbons, Alastair T; Goodacre, Sara L; Pekár, Stano
Abstract: There is a growing evidence that consistent interindividual differences in behavior, that is, behavioral types, can play an important role in key ecological processes such as predator–prey interactions, which in turn can have direct implications on biological control. Behavioral types of generalist predators may affect these interactions through individual differences in predators' prey preferences and the breadth of predators' trophic niches. This study examined how the multivariate nature of behavior, namely foraging aggressiveness, activity level, and risk-taking behavior, determines prey selection and trophic niche of the generalist agrobiont spider Philodromus cespitum . In laboratory experiments, we determined the repeatability of these behaviors and the preference between crickets, moths, fruit flies, and collembolans. We found that all three behaviors were moderately to strongly repeatable but there were no correlations between them, thus they did not form a behavioral syndrome. Only foraging aggressiveness influenced the prey selection of philodromid spiders and the more aggressive individuals had wider trophic niches because they incorporated prey that were more difficult to capture in their diet. In addition, more aggressive individuals killed a greater quantity of particular prey types while other prey types were killed at a similar rate by both aggressive and nonaggressive individuals. The differences in philodromids' foraging aggressiveness, therefore, affected not only the overall prey density but also resulted in different prey community composition. As pest density and composition can both affect crop performance, further research needs to investigate how the interindividual behavioral differences of generalist natural enemies cascade down on the crops. Abstract : Individuals of a predator species can consistently differ in various behaviors, for example, in foraging aggressiveness, activity level, or risk-taking behavior. These behavioral differences between individuals may or may not translate in to the diet which the individuals choose. In a spider predator, only foraging aggressiveness influenced prey selection in that aggressive individuals had broader diet than the nonaggressive individuals because they captured prey that were more difficult to subdue.